Later Life Care Planning and Concerns of Transgender Older Adults in Canada. (July 2019) - Pang, Celeste; Gutman, Gloria; de Vries, Brian
While the particular health-care concerns of transgender people have been documented and transgender aging is an emerging area of scholarship, little is known about planning for later and end-of-life care among transgender older adults. As part of a larger project, focus groups and interviews were conducted with 24 transgender older adults (average age 70 years) living in five cities in Canada exploring their concerns and explicit plans for later life care. Three primary themes emerged: (a) "dealing with the day-to-day" reflecting economic precarity and transitioning in later life, (b) fractures and support within family and community, and (c) "there's a huge gap between principle and practice" reflecting mixed experiences and perceptions of health-care services. These themes suggest that effective promotion of care planning among older transgender persons requires an appreciation of the daily exigencies of their lives and the extent and nature of social support available to them.